Pellagroid Dermatitis in an Alcoholic and Hypothyroid Patient. A Case Report - Graciela Cabrera Acea; Cynthia Gómez Cabrera; Claudia Soler Morfa (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Pellagroid dermatitis is a condition resulting from the deficiency of niacin and/or tryptophan that causes dermatological, gastrointestinal and neurological symptoms. It is very rare in our country, a fact that motivated us to present this case. The patient was a 49-year-old white man diagnosed with pellagroid dermatitis. He also suffered from hypothyroidism, alcohol dependence and had poor eating habits due to his frequent drinking. He had a medical history of hypertension and presented cutaneous manifestations of pellagroid dermatitis. The erythematous and scaly manifestations were located on the back of both arms. They resembled scalded skin; some had an ulcerated and blistered center and were similar to those in the neck, deltoid region and other sites exposed to sunlight. The lesions were permanently cured after vitamin therapy and skin protection from solar radiation.